2020
DOI: 10.1038/s41585-020-0336-6
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth in urology after the COVID-19 pandemic

Abstract: In response to the COVID-19 pandemic, the need to safely provide patient care meant that many health-care providers rapidly implemented and integrated telehealth into their practice. However, telehealth will continue to be an integral part of urology after the pandemic and our field should embrace telehealth and develop strategies to overcome associated challenges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0
5

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 9 publications
0
38
0
5
Order By: Relevance
“…Elective surgeries have been suspended and even cancer cases have been postponed, with the hope that such delay will not have a negative impact on patient's outcome (9). Telemedicine has become an important tool, reducing the exposure of patients and clinicians, but only a small fragment of practitioners was prepared for this and most patients do not openly accept this new way modality of evaluation (10,11). As a result, urologists and other surgical specialists have been experiencing a tremendous impact on their income, especially those whose earnings are driven mostly from their private practice (12).…”
Section: Introductionmentioning
confidence: 99%
“…Elective surgeries have been suspended and even cancer cases have been postponed, with the hope that such delay will not have a negative impact on patient's outcome (9). Telemedicine has become an important tool, reducing the exposure of patients and clinicians, but only a small fragment of practitioners was prepared for this and most patients do not openly accept this new way modality of evaluation (10,11). As a result, urologists and other surgical specialists have been experiencing a tremendous impact on their income, especially those whose earnings are driven mostly from their private practice (12).…”
Section: Introductionmentioning
confidence: 99%
“…40 Telemedicine (video visit, virtual check-in, eVisit, and eConsult) not only provides zero risk urology services during a pandemic but also has the potential to grow into telemonitoring (cystoscopy, video-urodynamic, radiodiagnosis) and telesurgery (robotic surgery). 51 Based upon the risk grading, a study in Germany found that 54.1% of the patients in Germany were eligible (based on risk grading) and willing for tele-consultation for urology care that will ensure "contact-free continuity of care". 25 Besides convenience, efficiency, and cost-utility the long-term quality health care (efficacy, safety, and equity) provided by the telehealth is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Actualmente existe un volumen de publicaciones creciente sobre la pandemia COVID-19. Algunas de estas publicaciones abordan el impacto del SARS-CoV-2 en pacientes urológicos, pero no existe información sobre la percepción y el impacto de la teleconsulta en los pacientes en la especialidad de urología [4][5][6] .…”
Section: Introductionunclassified